Use of three different combinations for spinal anaesthesia on clinical and haematological parameters in goats - Canpolat, Ibrahim; Karabulut, Enis; Cakir, Sema (Mehria Publishers, 2017)
The aim of this study was to evaluate effectively of the combination of ketamine HCl -xylazine HCl, ketamine HCl -medetomidine HCl and bupivacain-morphine for spinal anaesthesia on clinical and haematological parameters in three groups (each group had 6 goats). Each goat in groups was given a dose of the drugs combination: Group 1; ketamine HCl at 2.5mg/kg and xylazine HCl at 0.05mg/ kg, group 2; ketamine HCl at 2.5 mg/kg and medetomidine HCl at 0.01 mg/kg, group 3; bupivacain at 2 ml and morhine 0.5 ml. The drugs were injected epidurally into the lumbosacral subarachnoid space. Begining of the skin analgesia and total duration of skin analgesia and duration of recumbency were measured timely. Rectal temperature (RT), heart rate (HR) and respiratory rate (RR) were intervaly recorded at pre-anesthesia and 30th, 60th, 90th, 120th minutes intervals. Pre-injection blood samples were obtained and repeated at 30th, 60th, 90th, 120th minutes intervals during anaesthesia and at 24 hours into the tubes with EDTA and than analyzed. The evaluated parameters were venous blood pH, blood gases (PaCO2, PaO2, etCO2, s02), Na, Cl, hematocrit (HCT), haemoglobin (HGB), bicarbonate (HCO3a, HCO3s). The onset of analgesia was 1.24 ±0.35 min. in (group 1, 1.08±0.22 min. in group 2) and 0.92±0.32 min. in group 3, respectively. Duration of the skin analgesia were 48±8.4 min. in group 1, 50±6.4 min. in group 2, and 55±9.6 min. in group 3, respectively. Duration of recumbency 80-200 min. in all groups. RT did not show any significant change. HR depression significantly (P < 0.05) in all combination groups and RR decression were recorded in groups 1 and 2. PaO2 decreased significantly all groups. PaCO2 increased significantly in groups 1 and 2. Serum electrolytes did not show any significant difference. The values were returned to normal at 24th hours in all groups. As a conclusion, The ketamine-xylazine, ketamine-medetomidine and bupivacain-morphine for spinal anaesthesia can be safely used in goats as it caused transient clinical and haemetological alterations. © 2017 IJVS. All rights reserved.
Keywords: Bupivacain; Goat; Ketamine; Medetomidine; Morphine; Spinal anesthesia; Xylazine